Improving elementary school motivation in learning science - Ice Muniwastia; Yanti Fitriaice Muniwastia; Yanti Fitria; Ardipal Ardipal (Fakultas Ilmu Pendidikan UNP)
This article was written based on the results of classroom action research on students' learning motivation elementary school. This study aims to describe the improvement of learning motivation of the fourth grade students of the elementary school by applying the model of Problem Based Learning.The research model used Classroom Action Research methods that take place in two research cycles. Each cycle consists of planning, execution, observation, and reflection.The data analysis is a combination of qualitative and quantitative.The data analysis is a combination of qualitative and quantitative. Subjects in this study were 32 students.The results showed that the application of Problem Based Learning model proved to increase the motivation of learning grade four elementary school students.